Functional Outcome of Distal Tibial Fractures Fixed with Distal Tibial Locking Plate using MIPPO Technique - Kumar Kundu, Nripen; Ahmed Miajee , Anwar; Dastider, Sathi (Medicine Today, 2023)
Introduction: Because of the extensive list of potential consequences, treating extra-articular distal tibia fractures is a daunting task for an orthopedic surgeon. This study was designed to evaluate the clinical and functional outcomes of minimally invasive plating for the treatment of distal tibial fractures. Materials and Methods: This prospective study was conducted at the Department of Orthopedic Surgery, Popular Medical College and Hospital, Dhaka during June 2021 to May 2022. A total of 20 patients with distal tibial fracture were selected for surgery and treated with minimally invasive plating. Afterwards, the patients' clinical and radiological outcomes were recorded. The ankle-hindfoot score developed by the American Orthopedic Foot and Ankle Society (AOFAS) was used to assess the functional outcomes. Results: In 15 of the 20 cases, radiological union took place between 18 and 22 weeks (mean 20.5 weeks); however, in 5 cases, union was delayed and required almost 26 weeks to establish. Four of the 20 cases experienced a superficial infection, while the remaining patients showed no further complications. According to the AOFAS score, our research showed that, out of 20 patients, 9 had excellent outcomes, 8 had good results, and 3 had acceptable results. Conclusion: Treatment of distal tibia fractures with locking plates by MIPPO technique is an effective method of therapy to achieve union and excellent functional results since it aids in the early restoration of ankle movement while reducing ankle stiffness. Medicine Today 2023 Vol.35(2): 114-117